2016
DOI: 10.14430/arctic4593
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Abundance of Cyamid “Whale Lice” (<i>Cyamus ceti</i>) on Subsistence Harvested Bowhead Whales (<i>Balaena mysticetus</i>)

Abstract: We present findings on the prevalence and abundance of cyamid ectoparasites (Cyamus ceti) or “whale lice” on bowhead whales (Balaena mysticetus) harvested for subsistence in the Bering, Chukchi, and Beaufort Seas from 1973 to 2015. Cyamids were present on 20% of the 673 whales that were examined for cyamid ectoparasites. Logistic regression was used to determine factors associated with cyamid prevalence. The probability of cyamid presence increased with age, length, and improving body condition, but decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…There are biological factors affecting skin condition that may explain why bowhead whales molt. One is that they may slough their skin to shed ectoparasites such as cyamids (i.e., whale lice) [ 42 , 43 ] and accumulated diatoms (i.e., phytoplankton) [ 44 ] that may damage their epidermis and potentially impede thermoregulation. Another possibility is that bowhead whales are shedding solar damaged skin [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are biological factors affecting skin condition that may explain why bowhead whales molt. One is that they may slough their skin to shed ectoparasites such as cyamids (i.e., whale lice) [ 42 , 43 ] and accumulated diatoms (i.e., phytoplankton) [ 44 ] that may damage their epidermis and potentially impede thermoregulation. Another possibility is that bowhead whales are shedding solar damaged skin [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…So far, mostly opportunistic findings were reported, describing cyamid infections on harbour porpoises and a white-beaked dolphin from the North Sea ( Stock, 1973a ; Fransen and Smeenk 1991 ; Lehnert et al, 2007 ), but also from more rarely observed visitors like a Northern bottlenose whale ( Hyperoodon ampullatus ) and a sperm whale ( Physeter macrocephalus ) ( Stock, 1973b ). Few systematic surveys on whale lice have been performed worldwide, e.g., for odontocetes on I. delphinii on pilot whales off the Faroe Islands ( Balbuena andRaga, 1991 ), and Syncyamus aequus on striped dolphins in the Mediterranean ( Fraija-Fernández et al 2017 ) and for baleen whales on Cyamus ceti on bowhead whales ( Baleana mysticetus ) ( Von Duyke et al, 2016 ), on C. boopis on humpback whales ( Megaptera novaeangliae ) ( Iwasa-Arai et al, 2018 ) and on C. ceti , C. kessleri and C. scammoni on gray whales ( Callahan, 2008 ). Whale lice prevalence in the present study was low compared to other commonly occurring parasite species in harbour porpoises in the North Sea, like gastric and lung nematodes (30–90%), or hepatic trematodes (50%, Lehnert et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whale lice prevalence in the present study was low compared to other commonly occurring parasite species in harbour porpoises in the North Sea, like gastric and lung nematodes (30–90%), or hepatic trematodes (50%, Lehnert et al, 2005 ). For odontocetes, whale lice prevalence of 27% on striped dolphins in the Mediterranean ( Fraija‐Fernández et al, 2017 ), and 30% on Faroe Island pilot whales ( Balbuena and Raga, 1991 ) have been reported and for baleen whales a prevalence of 20% was for bowhead whales from the Bering, Chukchi, and Beaufort Seas ( Von Duyke et al, 2016 ). A striking difference in whale lice prevalence was found between the harbour porpoises stranded in the Netherlands and those stranded on the German coastline, with a lower prevalence observed in Germany (1.6%) compared to the Netherlands (7.6%) in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cyamids have no free-swimming stage, infection depends on direct physical contact between whales. Cyamid prevalence and body burden of BCB bowhead whales is around 20% with an average body burden of 1–5 whale lice ( Von Duyke et al, 2016 ). Heavy cyamid infestations (~50–100 cyamids) are uncommon, but have been observed in bowhead whales entangled in fishing gear, bowhead whales with old entanglement injuries, and previously harpooned bowhead whales.…”
Section: Infectious Diseasesmentioning
confidence: 99%